A new species of hedgehog-lizard of the genus Echinosaura (Squamata: Gymnophthalmidae) from Colombia and Panama with a reevaluation of the conservation status of the genus - Vásquez-Restrepo, Juan D.; Daza, Juan M. (Zootaxa, 2025)
The gymnophthalmid semi-aquatic lizards of the genus Echinosaura have been subject to taxonomic scrutiny in recent years. Here, we combine previously available and new morphological and phylogenetic evidence to describe a new species formerly known under the name E. palmeri. Our results are consistent with previous phylogenetic hypotheses and recover an overlooked evolutionary lineage which is both morphologically and genetically different from the other ones currently recognized within the genus. This species is diagnosable based on external and hemipenial morphology and is phylogenetically related to E. centralis, E. palmeri, and E. panamensis. The new species inhabits the northern portion of the Pacific region in Colombia and the Darien zone between Colombia and Panama. We also re-evaluate and propose a new IUCN extinction risk categorization for the nine species in the genus, assessing three uncategorized species, removing two species from a threatened category, and including a previously considered Least Concern species into a threatened status.